2016
DOI: 10.1161/circgenetics.115.001096
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Lipid Levels and Lipid Change Over Time and Risk of Incident Hyperlipidemia in Chinese Populations

Abstract: Background-Multiple genetic loci associated with lipid levels have been identified predominantly in Europeans, and the issue of to what extent these genetic loci can predict blood lipid levels increases over time and the incidence of future hyperlipidemia remains largely unknown. Methods and Results-We conducted a meta-analysis of genome-wide association studies of lipid levels in 8344 subjects followed by replication studies including 14 739 additional individuals. We replicated 17 previously reported loci. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 30 publications
2
42
1
Order By: Relevance
“…Previous studies have shown the association between GCKR rs1260333 and lipid levels, triglyceride, insulin resistance and metabolic syndrome (35,36). But results of a study in a pediatric population have demonstrated that though this SNP was associated with hypertriglyceridemia in children, the triglyceride increasing allele has protective effect for insulin resistance (37).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown the association between GCKR rs1260333 and lipid levels, triglyceride, insulin resistance and metabolic syndrome (35,36). But results of a study in a pediatric population have demonstrated that though this SNP was associated with hypertriglyceridemia in children, the triglyceride increasing allele has protective effect for insulin resistance (37).…”
Section: Discussionmentioning
confidence: 94%
“…Rs1260326, which is a non-synonymous variant in GCKR, and rs1260333, located downstream of GCKR, were reported to have inverse effects on TG and glucose levels in European descent populations [26][27][28]. The association between these two SNPs and TG level is validated in Chinese and Japanese [29,30]. Moreover, TG-increasing alleles of GCKR variants rs1260326 and rs1260333 lowered insulin and HOMA-IR and reduced the risk of insulin resistance in Chinese [31].…”
Section: Discussionmentioning
confidence: 95%
“…This enzyme catalyzes the synthesis of retinoic acid from retinaldehyde and retinoic acid, the active derivative of vitamin A, is a hormonal signaling molecule that functions in normal organ development [35]. Variants of the ALDH1A2 gene was associated with lipid traits in previous several Asian studies [29,36]. The LIPC gene provides instructions for making hepatic lipase, which helps with the conversion of very low-density lipoprotein (VLDL) to LDL.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 69 loci associated with HDL-cholesterol–related traits in the present study, 16 loci—12q24.1 [24], 16q13 [15, 16], CETP [15, 16], APOA5 [16], LIPC [16, 17], HECTD4 [24], LILRB2 [8], LPL [15, 16], 8p21.3 [15, 16], LOC101928635 [10, 17], BUD13 [16], ZPR1 [23], ABCA1 [10, 16], 11q23.3 [16], OAS3 [24], and CD36 [25]—were previously shown to be related to the blood HDL-cholesterol level or hypo–HDL-cholesterolemia (Supplementary Table 17). Among the 32 loci associated with LDL-cholesterol–related traits in the present study, nine loci— APOE [26], APOC1 [27], APOB [16, 17], PCSK9 [17], PSRC1 [12, 28], CELSR2 [10, 16], 1p13.3 [16], ABO [17], and 9q34.2 [8, 17]—were previously shown to be related to the circulating LDL-cholesterol concentration or hyper–LDL-cholesterolemia (Supplementary Table 18). …”
Section: Resultsmentioning
confidence: 98%
“…Among the 24 loci associated with triglyceride-related traits in the present study, 13 loci— BUD13 [15], 11q23.3 [16], APOA5 [15, 16], ZPR1 [16], APOA4 [15, 17], LPL [15, 17], 8p21.3 [15, 18], SIK3 [19, 20], GCKR [16], 2p23 [17, 21], C2orf16 [22], 8q24.1 [23], and LOC101929011 [21]—were previously shown to be related to the circulating triglyceride level or hypertriglyceridemia (Supplementary Table 16). Among the 69 loci associated with HDL-cholesterol–related traits in the present study, 16 loci—12q24.1 [24], 16q13 [15, 16], CETP [15, 16], APOA5 [16], LIPC [16, 17], HECTD4 [24], LILRB2 [8], LPL [15, 16], 8p21.3 [15, 16], LOC101928635 [10, 17], BUD13 [16], ZPR1 [23], ABCA1 [10, 16], 11q23.3 [16], OAS3 [24], and CD36 [25]—were previously shown to be related to the blood HDL-cholesterol level or hypo–HDL-cholesterolemia (Supplementary Table 17). Among the 32 loci associated with LDL-cholesterol–related traits in the present study, nine loci— APOE [26], APOC1 [27], APOB [16, 17], PCSK9 [17], PSRC1 [12, 28], CELSR2 [10, 16], 1p13.3 [16], ABO [17], and 9q34.2 [8, 17]—were previously shown to be related to the circulating LDL-cholesterol concentration or hyper–LDL-cholesterolemia (Supplementary Table 18).…”
Section: Resultsmentioning
confidence: 99%